A New Comparison Principle for Impulsive Functional Differential Equations - Gang Li; Weizhong Ling; Changming Ding (Discrete Dynamics in Nature and Society)
We establish a new comparison principle for impulsive differential systems with time delay. Then, using this comparison principle, we obtain some sufficient conditions for several stabilities of impulsive delay differential equations. Finally, we present an example to show the effectiveness of our results.